Stranski liki v Sofoklovih tragedijah - Senegačnik, Brane (Primerjalna književnost, 2002)
Defining the supporting characters in Sophocles' tragedies, and their dramaturgical significance of Tiresias in Oedipus Rex. The article first deals with the problem of determining the main and supporting characters in plays, and outlines specific problems correlated to this issue in antique tragedy. A criterion for the determination of the status of characters in Sophocles' work is then proposed. The so-called dramatic climate is treated as an important element of dramatic reality. The significance of the supporting character is illustrated in the case of the blind soothsayer Tiresias in Oedipus Rex.
Keywords: Sophocles, 495-406 pr.n.št.; stara grška tragedija; dramski liki; Kralj Ojdip